Environmental Sanitation and PHBS Analysis of Stunting Incidents in Toddler in Paser District - Nor Aisyah Purnamasari; Mursid Raharjo; Yusniar Hanani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life (HPK). The direct causes of stunting in toddlers are a history of Low Birth Weight (LBW), food availability, household consumption patterns and infectious diseases in toddlers. Objective: The aim of this research is to analyze environmental sanitation and PHBS on the incidence of stunting in Paser Regency. Research Method: Correlative analytical research type, with a case control approach with a case population of 4,665 toddlers in 21 villages/subdistricts and for the sample using 1:1, that means a sample of 62 cases and 62 controls. Results: The results of this research are the variable ownership of healthy toilets, p-value 0.005 and OR=3.054, 95%CI 1.388-6.716), water quality (p-value 0.017 and OR=2.298, 95%CI 1.158-4.564), PHBS behavior (p-value 0.04 and OR=2.020, 95%CI 1.025-3.978) and SBABS variables (p-value 0.002 and OR=2.911, 95%CI 1.458-5.811) Conclusion: So it can be concluded that there is a significant relationship between latrine ownership, water quality, PHBS and SBABS behavior and the incidence of stunting in Paser Regency